2020
DOI: 10.3390/ijms21030755
|View full text |Cite
|
Sign up to set email alerts
|

Low Dose of Penfluridol Inhibits VEGF-Induced Angiogenesis

Abstract: Metastasis is considered a major burden in cancer, being responsible for more than 90% of cancer-related deaths. Tumor angiogenesis is one of the main processes that lead to tumor metastasis. Penfluridol is a classic and commonly used antipsychotic drug, which has a great ability to cross the blood–brain barrier. Recent studies have revealed that penfluridol has significant anti-cancer activity in diverse tumors, such as metastatic breast cancer and glioblastoma. Here, we aim to identify the effect of low dose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 60 publications
(83 reference statements)
0
7
0
Order By: Relevance
“…In particular, when the two types of cells were cocultured in a 3D hydrogel microenvironment, they showed satisfactory proliferation ability and reached the maximum on day 7. As described previously, VEGF promotes angiogenesis and increases vascular permeability, which plays a pivotal role in tumor angiogenesis (Srivastava et al, 2020). In particular, VEGFA is a major player in physiological and tumor-induced angiogenesis, and numerous human tumors, including GBM, have shown VEGFA overexpression (Andreozzi et al, 2014).…”
Section: Discussionmentioning
confidence: 83%
“…In particular, when the two types of cells were cocultured in a 3D hydrogel microenvironment, they showed satisfactory proliferation ability and reached the maximum on day 7. As described previously, VEGF promotes angiogenesis and increases vascular permeability, which plays a pivotal role in tumor angiogenesis (Srivastava et al, 2020). In particular, VEGFA is a major player in physiological and tumor-induced angiogenesis, and numerous human tumors, including GBM, have shown VEGFA overexpression (Andreozzi et al, 2014).…”
Section: Discussionmentioning
confidence: 83%
“… 60 , 115 In addition, PF has been shown to modulate the immunosuppressive TME in GBM by lowering the expression of MDSCs and increasing the expression of M1 macrophages 116 as well as regulating angiogenesis by inhibiting the VEGF-signaling pathway in ECs. 117 The specificity of PF as an integrin-targeting drug is not fully understood and therefore would be worthwhile to investigate in order to understand its implications in tumor and immune cells. Additionally, data have not yet been published showing the survival benefits of PF as a single agent in vivo, but the combination of PF with TMZ has shown sensitization of GSCs to the alkylating agent.…”
Section: Effect Of Integrin Inhibition On Ohsv Efficacymentioning
confidence: 99%
“…Collagen has been served as a biodegradable scaffold material and extensively employed in research on vascular regeneration studies, supporting and promoting angiogenesis . Prior research has shown that collagen regulates the migration and adhesion of endothelial cells by furnishing cell adhesion sites and facilitating cell-to-cell interactions. , Through binding to cell receptors, collagen initiates a cascade of cellular signaling pathways that impact various functions, including the survival, proliferation, and migration of vascular endothelial cells. , Additionally, collagen can modulate inflammatory responses, contributing to wound healing and the reconstruction of endothelial function . ADSCs are a type of multipotent stem cell found in adipose tissue, possessing the potential for multilineage differentiation.…”
Section: Introductionmentioning
confidence: 99%
“…30,31 Through binding to cell receptors, collagen initiates a cascade of cellular signaling pathways that impact various functions, including the survival, proliferation, and migration of vascular endothelial cells. 32,33 Additionally, collagen can modulate inflammatory responses, contributing to wound healing and the reconstruction of endothelial function. 34 ADSCs are a type of multipotent stem cell found in adipose tissue, possessing the potential for multilineage differentiation.…”
Section: Introductionmentioning
confidence: 99%